Effects of Protein Supplementation on Performance and Recovery in Resistance and Endurance Training - Cintineo, Harry P.; Arent, Michelle A.; Antonio, Jose; Arent, Shawn M. (Frontiers in Nutrition, 2018)
There is robust evidence which shows that consuming protein pre- and/or post-workout induces a significant rise in muscle protein synthesis. It should be noted, however, that total daily caloric and protein intake over the long term play the most crucial dietary roles in facilitating adaptations to exercise. However, once these factors are accounted for, it appears that peri-exercise protein intake, particularly in the post-training period, plays a potentially useful role in terms of optimizing physical performance and positively influencing the subsequent recovery processes for both resistance training and endurance exercise. Factors that affect the utility of pre- or post-workout feeding include but are not necessarily limited to: training status (e.g., novice versus advanced, or recreational versus competitive athlete), duration of exercise, the number of training sessions per day, the number of competitive events per day, etc. From a purely pragmatic standpoint, consuming protein post-workout represents an opportunity to feed; this in turn contributes to one’s total daily energy and protein intake. Furthermore, despite recent suggestions that one does not “need” to consume protein during the immediate (1 hour or less) post-training time frame, it should be emphasized that consuming nothing offers no advantage and perhaps even a disadvantage. Thus, based on performance and recovery effects, it appears that the common-sense approach would be to have athletes consume protein post-workout/competition.